Microwave-assisted roasting time on Ilmenite Bangka Belitung extraction using hydrometallurgical method - Mutakin, Ikbalul; Suryana, Risa; Septiani, Eka Lutfi; Arutanti, Osi; Widiyandari, Hendri (Universitas Sebelas Maret, 2024)
Titanium Dioxide (TiO2) was extracted from Bangka Ilmenite through a hydrometallurgical process employing the microwave-assisted method using a 20% HCl solution. The highest crystallinity percentage in XRD result, reaching 75%, was achieved after a roasting duration of 25 minutes, with a corresponding crystallite size of 35.57 nm at the TiO2-Anatase phase's peak intensity of 25.24°. Analysis of the extracted ilmenite revealed alterations in its compound composition, notably an increase in TiO2 content. The most substantial increase in TiO2 content, rising to 69.7% from 33.76%, was observed after 25 minutes of roasting. UV–Vis spectroscopy revealed an energy band gap of 2.329 eV.